Night & day - Connolly, John (New York, NY Emily Bestler Books/Atria, 2024)
New York Times bestselling author John Connolly, "one of the best thriller writers we have" (Harlan Coben, #1 New York Times bestselling author), returns with a shivery collection of supernatural tales. Filled with eerie surprises and dark delights, Night and Day takes us from the dusty shelves of an uncanny library filled with fictional characters to a bunker deep beneath the earth where scientists seek revenge on old Nazis; from an English marsh haunted by a mother and her son to a country house where a grieving widower finds comfort from a most unlikely source. Concluding with the author's account of how an obscure horror film brought him closer to his lost father, and how nostalgia can help to keep us sane, this is a collection that will move, entertain, and keep you reading late into the night.
The pilgrim's progress: a tale of the Caxton Private Lending Library & Book Despository -- And all the graves of all the ghosts -- The evenings with Evans -- Abelman's line -- The mire at Fox Tor -- The bear -- The flaw -- Unquiet slumbers: a tale of the Caxton Private Lending Library & Book Despository -- Our friend Carlton -- Horror express (extended edition).
Includes bibliographical references.
115233
Keywords: Demonology -- Fiction; Private investigators -- Fiction; Murder -- Investigation -- Fiction; Revenge -- Fiction; Horror tales, English; Short stories, English; Ghost stories; Folklore; Ghost stories; Short stories; Horror fiction; Paranormal fiction; Detective and mystery fiction; Thrillers (Fiction); Psychological fiction; Nouvelles